PREDICTION OF FORMATION OF CNS LESIONS IN NEWBORNS DELIVERIED AT 41 AND MORE WEEKS BY PACIENTS WITH HIGH PERINATAL RISK - Фильчакова, Оксана Николаевна; Кравцова, Елена Станиславовна; Бельницкая, Ольга Александровна; Кореновский, Юрий Владимирович (Mother and Baby in Kuzbass, 2019)
Purpose of the study – identification of risk factors for the formation of CNS lesions in newborn maternal with perinatal high risk in childbirth at 41 or more weeks. Materials and methods. 540 pairs of mother – newborn were inspected. From newborns of 540 women two groups were formed depending on the presence or absence of perinatal lesions of the central nervous system of moderate and severe. Results. Some clinical and paraclinical high risk factors for perinatal lesions of the central nervous system have been identified in newborns from mothers with more than 41 weeks of pregnancy. Conclusions. The clinical risk factors for perinatal lesions of the central nervous system in newborns from the high perinatal risk mothers in the period more than 41 weeks are: up to delivery – a history of abortion, hypertension, fetal growth restriction and hemodynamic Doppler; before delivery – prenatal rupture of membranes, and in labor – anomalies of uterine activity and the use of uterotonics at delivery. Sensitivity indicator STV on the result CTG does not exceed 76.9 % and a specificity of 36.0 % gives a lot of false positives.